Community resilience frameworks for building disaster resilient community in Malaysia - Sulaiman, Dr. Noralfishah; Wei, She Teo; Fernando, Prof. Terrence (Malaysian Institue, 2019)
Disasters cannot be prevented fully but their impacts and severity can be lessened through the application of certain frameworks. However, there is currently a lack of a robust framework in building the disaster resilient and sustainable communities in Malaysia. Malaysians are increasingly finding themselves not being spared from disasters especially flood events. In order to keep pace with these occurring disasters in Malaysia, Community Resilience Frameworks are the backbone strategies among various stakeholders and can assure non-futile efforts for building safer and more resilient communities. Community Resilience Framework sets out the drivers, existing good practices, scopes, aims and work streams respectively for a long-term programme designed to increase the disaster resilience of communities. This paper has attempted to review the existence of disaster resilient communities in detail. Some Community Resilience Frameworks in the context of natural disasters in Malaysia will also be discussed. In this paper, literature is used as a foundation for a new insight contribution. A document analysis method on relevant policies and literatures also been adopted. It is envisaged that the findings of this study could be clinically useful for building a disaster resilient community and also closing the gaps in disaster risk reduction (DRR) in Malaysia